Nanopore adaptive sampling accurately detects nucleotide variants and improves the characterization of large‐scale rearrangement for the diagnosis of cancer predisposition - Sandy Chevrier; Corentin Richard; Marie Mille; Denis Bertrand; Romain Boidot (Clinical and Translational Medicine)
Abstract Background Molecular diagnosis has become highly significant for patient management in oncology. Methods Here, 30 well‐characterized clinical germline samples were studied with adaptive sampling to enrich the full sequence of 152 cancer predisposition genes. Sequencing was performed on Oxford Nanopore (ONT) R10.4.1 MinION flowcells with the Q20+ chemistry. Results In our cohort, 11 samples had large‐scale rearrangements (LSR), which were all detected with ONT sequencing. In addition to perfectly detecting the locus of the LSR, we found a known MLPA amplification of exon 13 in the BRCA1 (NM_7294) gene corresponded to a duplication in tandem of both exons 12 and 13 of the reference NM_7300. Similarly, in another sample with a known total deletion of the BRCA1 gene, ONT sequencing highlighted this complete deletion was the consequence of a large deletion of almost 140 000 bp carrying over five different genes. ONT sequencing was also able to detect all pathogenic nucleotide variants present in 16 samples at low coverage. As we analyzed complete genes and more genes than with short‐read sequencing, we detected novel unknown variants. We randomly selected six new variants with a coverage larger than 10× and an average quality higher than 14, and confirmed all of them by Sanger sequencing, suggesting that variants detected with ONT (coverage >10× and quality score >14) could be considered as real variants. Conclusions We showed that ONT adaptive sampling sequencing is suitable for the analysis of germline alterations, improves characterization of LSR, and detects single nucleotide variations even at low coverage. Key points Adaptive sampling is suitable for the analysis of germline alterations. Improves the characterization of Large Scale Rearrangement and detects SNV at a minimum coverage of 10x. Allows flexibility of sequencing.